Role of Inflammatory Markers in Early Diagnosis of Neonatal Sepsis; C-Reactive Protein or Procalcitonin or Red Cell Distribution Width; A Hospital-Based Study - Bai, Prinka; Rais, Heena; Asif, Rabia; Anwar, Tayyaba; Kumari, Sandhiya; Azeem, Masab (Pakistan Armed Forces Medical Journal, 2023)
Objective: To find out the utilization of C-reactive protein (CRP), Procalcitonin (PCT) and red cell distribution width (RDW) in diagnosing neonatal sepsis considering blood culture findings as gold standard.Study Design: Cross-sectional validation study.Place and Duration of Study: Neonatal Intensive Care Unit (NICU) of Dr Ziauddin Medical University, Karachi Pakistan, from Feb to Jul 2022.Methodology: A total of 42 neonates of either gender with the clinical diagnosis of neonatal sepsis were enrolled. Demographical and clinical characteristics of all neonates were noted at the time of enrollment. A blood sample of 5 ml was withdrawn for the evaluation of CRP, PCT and RDS. The association of different inflammatory markers with the outcome (neonatal sepsis) was assessed.Results: In 42 neonates, the mean age was 7.24±9.24 days, and 26 (61.9%) neonates were boys. Respiratory distress, reluctance to feed and hypoglycemia were the most frequent clinical presentations observed (19,45.2%), (14,33.3%) and (8,19.0%) neonates, respectively. Mean CRP levels among blood culture positive and negative neonates were 40.02±57.84mg/dl and 7.57±13.34 mg/dl, respectively, while the difference was statistically significant (p=0.0068). RDW (p=0.6488) and procalcitonin (0.9021) levels were not statistically significant differences among positive and negative neonates of blood culture.Conclusion: The CRP was a significant predictor of neonatal sepsis, while RDW and procalcitonin did not have a significant relationship with early prediction of neonatal sepsis.